On the Pristine Image of Honest and Ideal Political Order: (Review of Justinas Dementavičius’ book Tradicijos palikimas: centro dešinės ideologinė vaizduotė Lietuvoje: monografija, Vilnius: Vilniaus universiteto leidykla, 2023. – 448 p.) (Parliamentary Studies, 2022)
The monograph by Justinas Dementavičius, “Tradicijos palikimas: centro dešinės ideologinė vaizduotė Lietuvoje” (The Legacy of Tradition: The Ideological Imagination of the Center Right in Lithuania; Vilnius: Vilnius University Press, 2023), offers a panorama of the conservative center-right ideological imagination in Lithuania. Instead of exploring the practical party politics, the author of the book examines the tradition of center-right ideology from the late 19th century to the present day. Using a paradigmatic intellectual or groups of intellectuals, Dementavičius skillfully reveals the history of center-right ideas in Lithuania, highlighting the differences between the worldview and ideology of Christian democracy and conservatism, of Catholic nationalism and ‘cosmopolitan (Western)’ conservatism, and showing the transformation of a worldview into ideology. The monograph lacks a deeper justification of why the author has chosen the case of the center-right political imagination in Lithuania. This shortcoming comes at a price: the book gives the impression that there is no need for alternative—liberal and socialist—ideologies, because the correct conservatism covers everything, i.e., traditions and innovative drive, a strong attitude and stance, as well as spiritual ideals.
Keywords: a history of political thought; Lithuanian ideological imagination; center right; Christian democrats; conservatism; nationalism